Stability of salmon calcitonin against trypsin, chymotrypsin and neutrophil elastase in human lung epithelial cells - EHRHARDT, CARSTEN; BAGINSKI, EVE LEONIE; BUCKLEY, STEPHEN (My University, 2010)
At least three enzymes (i. e., trypsin, chymotrypsin and neutrophil elastase) are responsible for the degradation of salmon calcitonin (sCT) in the human body. Here, we investigated how these proteinases affect drug disposition of sCT in the lungs.
Sci Pharm
8th Central European Symposium on Pharmaceutical Technology
PUBLISHED
Graz, Austria
Keywords: Pharmacology; salmon calcitonin